Influencer Marketing as a Modern Phenomenon Creating a New Frontier of Virtual Opportunities - Kádeková, Zdenka; Holienčinová, Mária (Communication Today, 2018)
Social media influencers are winning over the Internet with their outstanding work and presence. Their opinions have a powerful impact on people, especially on young generation. We can mark them as a modern phenomenon that has seen a huge increase in cooperation with marketing agencies over recent years. More and more people are following such influencers so that they do not miss out on their content. Brands flock to such influencers for mentions, reviews and recommendations. Even though influencer marketing is a relatively new strategy, it continues to be a viable solution for marketers who are willing to think outside the box while building relationships with their target market. The aim of the study is to offer a comprehensive reflection on influencer marketing opportunities and determine the impact of influencers on consumer behaviour of Generations Y and Z. We wanted to find out whether influencers, who promote products, can attract potential customers and encourage them for purchase, as well as find differences between the given consumer generations. In order to meet the objectives of the study, own research was conducted (459 respondents from the Slovak Republic belonging to Generations Y and Z were involved in the inquiry). The research findings confirm that there are significant differences between the above mentioned consumer generations in the area of impact of influencers on consumer behaviour, which leads to different marketing opportunities. For statistical processing of the results, we used the Kruskal-Wallis Test, Kolmogorov-Smirnov Test, Fisher’s Exact Test and Dunn’s Test of Contrasts.